COMPARATIVE ANALYSIS OF INITIAL ESTIMATES AND FINAL OUTCOMES IN GLOBAL VS. LOCAL PROJECTS: SURVEY ANALYSIS - Sarsembiyev, Z. (Farabi Journal of Social Sciences, 2024)
This study examines the differences between the initial project estimates and the final outcomes in both global and local projects, specifically focusing on Kazakhstan. The goal of this research is to address this gap in existing research by comparing the initial estimates and the final deliverables in global and local projects. The study used a survey methodology to collect data from project managers with experience in both global and local projects. Significant differences were found in project management challenges and outcomes: global projects are more prone to cost overruns, schedule delays, and adverse impacts from scope changes compared to local projects. These findings highlight the complexity of managing global projects, emphasizing the need for enhanced planning, risk management, and communication strategies. The methodology involved distributing a detailed questionnaire via Google Forms in Russian and English, targeting professionals through various online platforms. Statistical analysis of the quantitative data and thematic analysis of qualitative responses provided a comprehensive view of the project management landscape. The key findings indicate that global projects encounter more challenges in sticking to their budgets and schedules and that changes in scope have a particularly strong negative impact. This research adds valuable insights that can help in developing customized project management practices for global settings. Future studies could broaden the scope to include various industries and regions in order to improve best practices for achieving project success on both a global and local level. Keywords: Comparative analysis, global projects, local projects, project estimates, project outcomes. Information about the author: Sarsembiyev Zhanbolat - MA. Business School, Kazakh-British Technical University (Almaty, Kazakhstan, e-mail: z_sarsembiyev@kbtu.kz)